Effect of Chlorogenic Acid on the Physicochemical and Functional Properties of Coregonus Peled Myofibrillar Protein through Hydroxyl Radical Oxidation - Xin Guo; Hengheng Qiu; Xiaorong Deng; Xiaoying Mao; Xiaobing Guo; Chengjian Xu; Jian Zhang (Molecules, 2019)
The effects of chlorogenic acid (CA) (6, 30, and 150 μM/g protein) on the physicochemical and functional properties of Coregonus peled myofibrillar protein (MP) through oxidation using a hydroxyl radical oxidation system (0.01 mM FeCl3, 0.01 mM Asc, and 1 mM H2O2) were investigated. The result showed that CA inhibited the increase in protein carbonyl content but did not prevent losses in sulfhydryl and free amine contents caused by oxidation. The presence of CA also increased conformational changes in the secondary and tertiary structures of oxidized MP. Oxidized MP containing 6 μM/g CA had superior functional properties (solubility, emulsifying, foaming, and gel properties), while oxidized MP containing 150 μM/g CA aggregated, resulting in insolubility and a poor gel network.